2023
DOI: 10.1038/s41598-023-38544-5
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 entry into and evolution within a skilled nursing facility

Abstract: SARS-CoV-2 belongs to the family Coronaviridae which includes multiple human pathogens that have an outsized impact on aging populations. As a novel human pathogen, SARS-CoV-2 is undergoing continuous adaptation to this new host species and there is evidence of this throughout the scientific and public literature. However, most investigations of SARS-CoV-2 evolution have focused on large-scale collections of data across diverse populations and/or living environments. Here we investigate SARS-CoV-2 evolution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…We identified one episode of likely transmission of SARS-CoV-2 from one resident to another, but there were no documented transmissions from residents to employees. Our findings are consistent with previous studies that identified nursing home employees as a primary source of transmission of SARS-CoV-2 to co-workers and residents [ 3 , 6 , 7 , 9 ]. Healthcare employees in hospital and outpatient settings have also been implicated as a frequent source of transmission to co-workers [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We identified one episode of likely transmission of SARS-CoV-2 from one resident to another, but there were no documented transmissions from residents to employees. Our findings are consistent with previous studies that identified nursing home employees as a primary source of transmission of SARS-CoV-2 to co-workers and residents [ 3 , 6 , 7 , 9 ]. Healthcare employees in hospital and outpatient settings have also been implicated as a frequent source of transmission to co-workers [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Preventing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in nursing home residents is a priority because factors such as age, frailty, and comorbid illnesses place them at high risk for adverse outcomes [2]. Pre-symptomatic and asymptomatic individuals may contribute substantially to transmission in long-term care facilities [3][4][5][6][7][8]. Therefore, in addition to other control measures, serial testing of asymptomatic employees and residents has been recommended in outbreak settings [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations